Effects of land‐use change and rainfall in Sudano‐Sahelian West Africa on the diet and nestling growth rates of an avian predator. (17th November 2012) - Buij, Ralph; Folkertsma, Ingrid; Kortekaas, Kim; De Iongh, Hans H.; Komdeur, Jan; Sergio, Fabrizio
<x xml:space="preserve">Abstract</x> Raptor populations in Sudano‐Sahelian West Africa are being severely affected by widespread habitat alteration which depletes prey populations, potentially aggravated by changing rainfall patterns. We studied Grasshopper Buzzards Butastur rufipennis at nests in natural and transformed habitats in the Sudano‐Sahelian region of northern Cameroon to assess the effects of habitat transformation and rainfall on nestling diet and growth. Grasshoppers and small mammals were more frequently taken in natural habitat, whereas lizards were most frequently taken in transformed habitats. These dietary differences reflected differences in prey availability around nests in natural and transformed habitats. Land use was a significant predictor of asymptotic weight: nestlings in natural habitat attained a higher mass than those in transformed habitats, when potentially confounding variables such as hatch order, gender, hatch date, rainfall or the presence of siblings were taken into consideration. These results suggest that body condition at fledging was habitat‐dependent, with potential consequences for subsequent survival. However, we recorded no differences in caloric content of food delivered to nests in natural and transformed habitat, which was possibly related to prey caught during twilight hours. There was a positive relationship between precipitation levels during the nestling phase and nestling growth rate. We predict unfavourable future conditions for nestling growth of raptors in Sudano‐Sahelian savannas as a consequence of continued widespread habitat transformation and diminished rainfall.